Initial breastfeeding attitudes and practices of women born in Turkey, Vietnam and Australia after giving birth in Australia - Forster Della A; McLachlan Helen L (BMC, 2006)
Abstract Background Cultural variations exist in the proportion of women who breastfeed. For some cultural groups, migration to a new country is associated with a reduction in the initiation and duration of breastfeeding. This paper describes the initial breastfeeding attitudes and practices of women born in Vietnam, Turkey and Australia who gave birth in Australia. Methods The study included 300 women: 100 hundred Turkish-born, 100 Vietnamese-born and 100 Australian-born women who had given birth in a large public, tertiary referral maternity hospital between January 1998 and May 1999 in Melbourne, Australia. Women were interviewed in hospital, between 24 hours after the birth and discharge from hospital. Data were collected using a structured questionnaire with some open-ended questions. Only women who had a normal vaginal birth and who gave birth to a healthy baby were included in the study. Results Almost all Turkish women initiated breastfeeding (98%) compared with 84% of Australian women. Vietnamese women had the lowest rate of breastfeeding initiation (75%), perceived their partners to be more negative about breastfeeding and did not value the health benefits of colostrum to the same extent as the other two groups. Forty percent of Vietnamese women gave their baby formula in hospital. The results of this study add to the previously reported finding that immigrant Vietnamese women have low breastfeeding rates compared with other groups. Conclusion Despite the Baby Friendly status of the hospital where the study was conducted, major differences were found in breastfeeding initiation. Future research should develop and test interventions aimed at increasing breastfeeding initiation in Vietnamese women where initiation is low.